Bank-firm relationships and the performance of non-financial firms during the financial crisis 2008-09: Microeconometric evidence from large-scale firm-level data - Kim Abildgren; Birgitte Vølund Buchholst; Jonas Staghøj (Danmarks Nationalbank, 2011)
Utilising a unique data set with annual accounts from around 37,000 Danish non-financial firms spanning one and a half decade or so, we offer microeconometric evidence on bankfirm relationships and the performance of non-financial firms during the financial crisis 2008-09. Two major conclusions are drawn from the analysis. First, the probability of default during the financial crisis 2008-09 was significantly higher for firms with a weak bank than for comparable firms with a sound bank. Second, non-defaulting firms with a weak bank did not have a lower return on assets during the financial crisis 2008-09 than comparable firms with a sound bank. Taken together, these results may indicate the presence of heterogeneous effects of having a weak bank with significant negative effects on the economic performance for some firms but insignificant effects for the broad mass of firms.
Keywords: E44; G21; G33; 330; Financial crisis; Bank-firm relationships; Probability of default; Firm survival; Unternehmensfinanzierung; Bank; Unternehmenserfolg; Insolvenz; Finanzkrise; Dänemark